Challenges and Strategies to Mitigate Problematic Social Media Use in Psychiatric Disorders. Issue 6 (November 2021) - Macenski, Christina L.; Hamel, Matthew P.; McDougle, Christopher J.; Thom, Robyn P.
Abstract : Learning objectives: After participating in this activity, learners should be better able to: Outline and discuss strategies to mitigate problematic social media use in psychiatric disorders Identify solutions to encourage healthy use Abstract: Social media has been found to contribute to a variety of different psychiatric disorders, with recent research showing a complex relationship between social media use and mental health outcomes. This article outlines how the strategies that social media sites utilize to increase user engagement can differentially affect individuals with psychiatric disorders, and proposes solutions that may promote more healthy use. With these aims in view, the article (1) delineates the strategies, often unrecognized, that social media sites use to increase user engagement, (2) highlights how these strategies can affect individuals with psychiatric disorders, and (3) proposes novel solutions to encourage healthy use. The first step to creating innovative and universal interventions is to understand the challenges faced by individuals with psychiatric disorders when using social media.